Semiotics of Happiness: Rhetorical Beginnings of a Public Problem - Ashley Frawley (Bloomsbury Academic, 2015)
The Semiotics of Happiness is a research monograph examining the rise of happiness (and its various satellite terminologies) as a social and political issue, exploring its origins in the US and subsequent spread into the UK and across the globe. The research takes as its starting point the development of discussions about happiness in UK newspapers in which dedicated advocates began to claim that a new science of happiness had been discovered and argued for social and political change on its behalf. Through an in-depth analysis of the rhetoric and activities of these influential ‘claims-makers’, I argue that happiness became a serious political issue not because of a growing unhappiness in society nor a demand ‘on the ground’ for new knowledge about it, but rather because influential and dedicated ‘insiders’ took the issue on at a cultural moment when problems cast in emotional terms were particularly likely to make an impact. Emerging from the analysis is the observation that, while apparently positive and light-hearted, the concern with happiness implicitly affirms a ‘vulnerability’ model of human functioning, encourages a morality of low expectations, and in spite of the radical language used to describe it, is ultimately conservative and ideally suited to an era of ‘no alternative’ (to capitalism).